Pan-cancer landscape of CD274 (PD-L1) copy number changes in 244 584 patient samples and the correlation with PD-L1 protein expression. Issue 5 (10th May 2021) - Huang, Richard S.P.; Murugesan, Karthikeyan; Montesion, Meagan; Pavlick, Dean C.; Mata, Douglas A.; Hiemenz, Matthew C.; Decker, Brennan; Frampton, Garrett; Albacker, Lee A.; Ross, Jeffrey S.
Abstract : Introduction: Several studies have shown clinical outcomes data that support the use of CD274 (PD-L1 ) copy-number (CN) gains and/or losses as a biomarker for immune checkpoint inhibitor (ICPI). Here, we present the landscape of CD274 CN changes across a large cohort of solid tumor cases and correlate these with PD-L1 protein expression by immunohistochemistry. Methods: We analyzed all cases that underwent comprehensive genomic profiling (CGP) testing at Foundation Medicine between August 2014 and June 2020. CD274 CN changes were correlated with PD-L1 expression in tumor types where there were Food and Drug Administration approved companion diagnostic (CDx) claims and the CDx assay was used to assess PD-L1 expression. Results: In all, 244 584 samples representing 290 solid tumor types were included in the study. Overall, 17.6% (42 983/244 584) had CD274 CN gains (>specimen ploidy), 44.6% (108 970/244 584) were CD274 CN neutral, and 37.9% (92 631/244 584) had CD274 CN loss. Using different CN cut offs to define CD274 positivity resulted in different prevalence estimates: ploidy +1, 17.4% (42 636/244 584); ploidy +2, 6.2% (15 183/244 584); ploidy +3, 2.2% (5375/244 584); ploidy +4, 1.1% (2712/244 584); and ploidy +8, 0.2% (434/244 584). The prevalence of CN changes and CN positivity varied based on tumor type. CD274 CN gains were significantly associated with PD-L1 positivity in NSCLC, urothelial carcinoma, breast carcinoma, cervical carcinoma, esophagus squamous cell carcinoma (SCC) and head and neck SCC (ORs 3.3, 3.0, 2.0, 4.5. 3.8, 8.4, 1.4, respectively; p<0.05) and with microsatellite instability status in only clinically relevant tumor types (gastric adenocarcinoma, colorectal adenocarcinoma, uterine endometrial adenocarcinoma, esophageal adenocarcinoma and gastroesophageal junction adenocarcinoma (OR: 5.2, 1.9, 3.2, 3.7 and 6.5, respectively; p<0.05)). Conversely, CD274 CN changes were not significantly correlated with tumor mutational burden in almost all the tumor types. Conclusion: CD274 CN changes and PD-L1 expression were highly correlated in multiple tumor types. These prevalence data on CD274 CN changes across a large cohort of different solid tumors can be used to design future clinical studies to assess whether CD274 CN changes could be a potential biomarker for ICPI.